Clipless Cholecystectomy in Adult and Pediatric Populations: Harmonic versus LigaSure Sealing - Sayed Ahmed Elhady Abdelmonem (Al-Azhar University, Faculty of Medicine (Damietta), 2021)
Background: Laparoscopic cholecystectomy is the commonest surgical intervention in adults and pediatrics. The controversy still exists about the ideal sealing system. Aim of the work:  The study aimed to evaluate the Harmonic scalpel and the LigaSure in laparoscopic clipless cholecystectomy in adults and pediatrics. Patients and methods: 60 adults and 30 pediatric patients were selected from our institution and scheduled for total clipless laparoscopic cholecystectomy, either by Harmonic or LigaSure sealing system. Preoperatively, all patients were evaluated by history taking, clinical examination, Lab investigation, and ultrasound examination. Demographic, operative, and postoperative data were documented. Results: Both groups of sealing systems were comparable regarding demographics, operative time, blood loss, postoperative pain, and complications.  In adult patients, 6.7% had complications [bile leak and common bile duct injury] in the harmonic group. In contrast, in the LigaSure group, 10.0% had complications [pneumonia in 3.3% and common bile duct injury with bile leak in 6.7%]. On the other hand, no bile leak or common bile duct injury was reported in the pediatric age group. The majority of pediatrics had chronic hemolytic anemia. Conversion to open in pediatrics was reported in 2 patients in harmonic and none in the LigaSure group. Surgical site infection was reported in 1 patient in LigaSure, while pneumonia was reported in 2 patients in the harmonic group. Conclusion: LigaSure and Harmonic sealing systems are effective and safe in total clipless cholecystectomy in adult and pediatric populations.